2019
DOI: 10.1002/slct.201902767
|View full text |Cite
|
Sign up to set email alerts
|

NaBH4In‐situ Reduced Cobalt Catalyst Supported on Zeolite A for 1‐Hexene Hydroformylation

Abstract: Zeolite A with different pore sizes (3 A, 4 A and 5 A) were selected as supports for preparing a series of cobalt catalysts through wetness impregnation method, using NaBH 4 as an insitu reducing agent, but without further reduction. X-ray photoelectron spectra (XPS) confirmed the reduction of cobalt. Transmission electron microscopy (TEM) images revealed that the cobalt nanoparticles were formed evenly on the zeolite structure by our rapid synthesis method. The catalytic activity of the prepared catalysts was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Copyright 2016 Elsevier B.V. Panels b and c were reproduced with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: Research Progress For Heterogeneous Hydroformylation By Coba...mentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2016 Elsevier B.V. Panels b and c were reproduced with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: Research Progress For Heterogeneous Hydroformylation By Coba...mentioning
confidence: 99%
“…The model diagram of the Co 3 O 4 nanocrystal catalyst was reproduced with permission from ref . Copyright 2020 Elsevier, Ltd. Model zeolite A was reproduced with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: Introductionmentioning
confidence: 99%
“…Tsubaki et al [91] prepared a series of zeolites with different pore sizes (3 Å, 4 Å and 5 Å) impregnated with cobalt nanoparticles catalysts using NaBH 4 as a reducing agent. The catalytic activity of the prepared catalysts was investigated in the hydroformylation of hex-1-ene (110°C, 50 bar CO/H 2 ), where conversions up to 92 % and 74 % heptanal selectivity were obtained.…”
Section: Metal Complexes and Metals Onto Solid Supportsmentioning
confidence: 99%
“…Tsubaki et al [91] . prepared a series of zeolites with different pore sizes (3 Å, 4 Å and 5 Å) impregnated with cobalt nanoparticles catalysts using NaBH 4 as a reducing agent.…”
Section: Reusable Hydroformylation Catalystsmentioning
confidence: 99%
“…The hydroformylation of alkenes is believed to be one of the largest scale industrial applications for the synthesis of aldehydes, which are valuable final products and intermediates in the synthesis of bulk chemicals, such as alcohols, acids, esters and amines, and other chemicals. The largest single primary product among all hydroformylation chemicals is butanal, which is mainly used in the production of dioctyl phthalate (DOP), a plasticizer that is widely used to impart softness and flexibility to normally rigid polyvinyl chloride (PVC) applications. Owing to the environmental pollution and toxicity of the DOP, diisononyl phthalate (DINP) produced from isononylaldehyde is increasingly being used to replace DOP as the higher performance and environment-friendly plasticizer of PVC polymers. , Among the methods for the synthesis of isononylaldehyde, hydroformylation of diisobutylene is one of the most powerful routes for the manufacture of isononylaldehyde. , Homogeneous cobalt complexes are extensively applied in the synthesis of isononylaldehyde due to their high activity, low cost, abundance, and affordability . In light of the inherent drawbacks of separating and recycling homogeneous catalysts, the use of heterogeneous catalysts for hydroformylation of diisobutylene would be an attractive choice owing to the convenience of recovering and recycling the catalysts. , Nevertheless, the heterogeneous ligand-free cobalt catalyst has a lower activity and selectivity for olefin hydroformylation reaction (Scheme a). To improve the catalytic performance of the heterogeneous cobalt catalysts, constructing Co-based bimetallic nanoparticles with additional noble metals has drawn much attention (Scheme b). Zhang and co-workers observed that the addition of a small amount of Ru could remarkably improve the catalytic activity and selectivity of Co/SiO 2 catalyst in the hydroformylation of 1-hexene, the conversion of 1-hexene increased from 33% to 50%, and selectivity to heptanal was enhanced from 14.6% to 59.4% under 5 MPa syngas at 130 °C . The Co–Pd/SiO 2 catalyst exhibited 89.7% conversion of 1-hexene and 77.9% selectivity to heptanal in the hydroformylation of 1-hexene under 5 MPa syngas at 130 °C, while 20.8% conversion of 1-hexene with 85.7% selectivity to heptanal was afforded with the conventional Co/SiO 2 catalyst .…”
Section: Introductionmentioning
confidence: 99%